Property Rights over Marital Transfers. (26th May 2015) - Anderson, Siwan; Bidner, Chris
Abstract: In developing countries, the extent to which women possess property rights is shaped in large part by transfers received at the time of marriage. Focusing on dowry, we develop a simple model of the marriage market with intrahousehold bargaining to understand the incentives for brides' parents to allocate the rights over the dowry between their daughter and her groom. In doing so, we clarify and formalize the "dual role" of dowry—as a premortem bequest and as a market clearing price—identified in the literature. We use the model to shed light on the intriguing observation that in contrast to other rights, women's rights over the dowry tend to deteriorate with development. We show how marriage payments are utilized even when they are inefficient, and how the marriage market mitigates changes in other dimensions of women's rights even to the point where women are worse off following a strengthening of such rights. We also generate predictions for when marital transfers will disappear and highlight the importance of female human capital for the welfare of women.